1992
DOI: 10.1002/chir.530040603
|View full text |Cite
|
Sign up to set email alerts
|

Formation of glycine conjugate and (–)‐(R)‐enantiomer from (+)‐(S)‐2‐phenylpropionic acid suggesting the formation of the coa thioester intermediate of (+)‐(S)‐enantiomer in dogs

Abstract: It has been proposed that the chiral inversion of the 2-arylpropionic acids is due to the stereospecific formation of the (-)-R-profenyl-CoA thioesters which are putative intermediates in the inversion. Accordingly, amino acid conjugation, for which the CoA thioesters are obligate intermediates, should be restricted to those optical forms which give rise to the (-)-R-profenyl-CoA, i.e., the racemates and the (-)-(R)-isomers. We have examined this problem in dogs with respect to 2-phenylpropionic acid(2-PPA). R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…Chiral R to S inversion has been observed for many profens in various speces. 25 The S to R inversion, on the other hand, is rare and is only demonstrated for ibuprofen in guinea pigs, 26 2-phenylpropionic acid in dogs, 27 and ketoprofen in mice. 28,29 The observed 6.7% of R-KT following administration of S-KT is also >1-2% of chiral impurity of the samples used.…”
Section: Discussionmentioning
confidence: 95%
“…Chiral R to S inversion has been observed for many profens in various speces. 25 The S to R inversion, on the other hand, is rare and is only demonstrated for ibuprofen in guinea pigs, 26 2-phenylpropionic acid in dogs, 27 and ketoprofen in mice. 28,29 The observed 6.7% of R-KT following administration of S-KT is also >1-2% of chiral impurity of the samples used.…”
Section: Discussionmentioning
confidence: 95%
“…Chen et al 7 reported equal extent of chiral inversion for both enantiomers of ibuprofen in guinea pigs. Tanaka et al 8 also observed that following administration of optically pure 2-phenylpropionic acid to dogs, the enantiomers concentrations reach the same level during the post-absorptive phase. These observations are consistent with those of ours and suggest the presence of a reversible metabolic inversion.…”
Section: Discussionmentioning
confidence: 91%
“…1), ibuprofen in the guinea pig 7 and 2-phenylpropionic acid in dogs. 8 The observation that ketoprofen undergoes bidirectional chiral inversion in the mouse has no apparent clinical relevance. Nevertheless, during pre-clinical stages, in choosing an animal model to study stereochemical aspects of drugs action and disposition, the information provided herein may prove useful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are commercially available as racemic mixtures with the exception of (S)-naproxen. It is known that only the (S)(+)-form of the NSAIDs is biologically active, [1][2][3][4] while the (R)(−)-form is partially converted to the (S)(+)-form. This fact has been demonstrated in many recent pharmacological studies.…”
mentioning
confidence: 99%